Zero-Knowledge Proofs (ZKP) And Smart Contracts For Automated Cross-Border Carbon Audit : A Decentralized Techno-Economic Framework - Aldi Adi Pratama (Feb Universitas Dirgantara Marsekal Suryadarma, 2026)
The rise of cross-border carbon regulations such as the European Union's Carbon Border Adjustment Mechanism (CBAM) demands emission verification systems trusted across multiple jurisdictions. However, conventional carbon audits remain manual, slow, costly, and prone to manipulation, while existing blockchain-based solutions require full disclosure of emissions data — conflicting with multinational corporations' need to protect confidential production information. This study proposes a decentralized framework integrating Zero-Knowledge Proofs (ZKP) and smart contracts to automate cross-border carbon auditing, employing a Design Science Research approach at the conceptual design level. The framework comprises four layers: data collection, proof generation, smart contract verification, and cross-jurisdictional interoperability, with Groth16 and the Perpetual Powers of Tau trusted setup as core cryptographic components. Techno-economic estimates derived from literature benchmarks indicate an on-chain verification cost of approximately 220,000 gas per transaction and verification times on the order of seconds to minutes, potentially far more efficient than conventional manual audit cycles that may span a year or more. This study also identifies privacy-adaptability and automation-legal flexibility trade-offs that must be managed in real-world implementation. Key contributions include the architectural design, economic feasibility analysis, and policy implications for regulators, with empirical validation through prototype development proposed as future research.